2022
DOI: 10.3847/1538-4357/ac9785
|View full text |Cite
|
Sign up to set email alerts
|

Searches for Neutrinos from Gamma-Ray Bursts Using the IceCube Neutrino Observatory

Abstract: Gamma-ray bursts (GRBs) are considered as promising sources of ultra-high-energy cosmic rays (UHECRs) due to their large power output. Observing a neutrino flux from GRBs would offer evidence that GRBs are hadronic accelerators of UHECRs. Previous IceCube analyses, which primarily focused on neutrinos arriving in temporal coincidence with the prompt gamma-rays, found no significant neutrino excess. The four analyses presented in this paper extend the region of interest to 14 days before and after the prompt ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…Advances in understanding require new diagnostics, e.g., observations of polarization or multiple messengers. However, so far, only upper limits on neutrino emission from either prompt or early afterglow emission have been set, suggesting a leptonic composition of the jet bulk (Abbasi et al 2022). Only a few GRBs (before GRB 221009A) have been detected in the very-highenergy regime and only one (short GRB) coincident with gravitational waves (Abbott et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in understanding require new diagnostics, e.g., observations of polarization or multiple messengers. However, so far, only upper limits on neutrino emission from either prompt or early afterglow emission have been set, suggesting a leptonic composition of the jet bulk (Abbasi et al 2022). Only a few GRBs (before GRB 221009A) have been detected in the very-highenergy regime and only one (short GRB) coincident with gravitational waves (Abbott et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…No neutrinos associated with individual GRBs have been detected so far (Abbasi et al 2012;Aartsen et al 2017;Abbasi et al 2022). Meanwhile, the energetic GRBs considered here are very luminous out in γ-rays, i.e., they could have been detected in most cases; see, e.g., Figure 1 in Kistler et al (2009).…”
Section: Point Source and Multiplet Constraintsmentioning
confidence: 75%
“…However, no statistically significant correlation was found in comparisons to date. The detectable neutrino fluence predicted from the simplest theoretical models was neither confirmed in the analysis of the IceCube data for individual bright GRBs (Gao et al 2013), nor identified in the model-independent stacking analysis searches performed on large samples of GRBs with different spectra (Abbasi et al 2012(Abbasi et al , 2022Aartsen et al 2016Aartsen et al , 2017. The recent detections of very-high-energy (>100 GeV) photons from GRBs (Abdalla et al 2019;Acciari et al 2019;Yong et al 2022) have prompted the searches for the associated multimessenger counterparts, but no neutrino detection from such GRBs has been confirmed so far.…”
Section: Introductionmentioning
confidence: 88%
“…GRBs are one of the prime targets of multi-messenger astronomy, as they have been detected in gravitational waves (GW170817/GRB 170817, Abbott et al 2017) and have been proposed as candidate sources of ultra-high-energy cosmic rays (UHECRs) and astrophysical neutrinos (e.g., Vietri 1995;Waxman 1995). While the contribution of typical luminosity GRBs during their prompt phase to the diffuse neutrino flux measured by IceCube has been constrained to 1% of the diffuse astrophysical neutrino flux (Abbasi et al 2022), the hypothesis that GRBs are UHECR sources cannot be ruled out yet (for a recent review, see Kimura 2022). In fact, GRBs populating the high end of the isotropic γ-ray energy distribution (E γ,iso > 10 54 erg) may provide the necessary energy output per event for powering UHECRs, requiring only a moderate baryonic loading (defined as the energy injected into nonthermal protons versus electrons) and without violating existing neutrino limits (Rudolph et al 2022).…”
Section: Introductionmentioning
confidence: 99%